Emerging zoonoses in Indonesia: implication for the future - Wandra, Toni (Faculty of Medicine, Trisakti University, 2020)
World Health Organization (WHO) defines zoonotic diseases (zoonoses) as those diseases and infections which are naturally transmitted between vertebrate animals and humans. More than 250 zoonoses have been described, over 60% of pathogens that cause diseases in humans are zoonoses of animals, and 75% of emerging infectious diseases. Most pandemics are caused by zoonoses.